Cultures for acid-fast bacilli: are we being good stewards? - Jennifer Hanrahan; Julie D. Sill; Patricia Ver Schneider; Jessica F. Copeland; Elsie Frimpongmaa Amoako-Kissi; Ogochukwu O. Ilobi; Angela J. Toepp (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract